Cardiovascular Endurance Level Of Physical Education Students At Tanjungpura University - fitriana puspa hidasari (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
Restrictions on social activities to online learning processes increase the potential for low body movements or sedentary life in Physical Education Students (PES). The purpose of this study was to determine the level of physical fitness of Tanjungpura University Physical Education students in terms of cardiorespiratory endurance. This study used a survey method. The data collection technique uses tests and measurements with the Multistage Fitness Test (MFT) instrument. The sample in this study were 33 male students. The data analysis technique used descriptive percentage. The results showed that none of the students had VO2Max at a very good level, there were 12.5% in the good category, and most of the students with a percentage of 62.5% were at a moderate level. While the remaining 18.75% and 9.37% are at the level of less and less. The conclusion of this study is that most Physical Education Students (PES) still have good physical fitness, while some students who are at a low level and very less need to be given motivation and understanding regarding the importance of fitness in sports students.